2023
DOI: 10.3390/app13021078
|View full text |Cite
|
Sign up to set email alerts
|

An Update to a Comprehensive Assessment of the Methods and Effectiveness of Resistance Training in Normobaric Hypoxia for the Development of Strength and Muscular Hypertrophy

Abstract: Background. Training muscle capacities in hypoxic conditions increases some manifestations, such as hypertrophy and muscle strength, due to a change in the muscle phenotype as a result of the activation of hypoxia-inducible factors (HIF). Despite the proven benefits of resistance training in hypoxic conditions that allow conjecture regarding the effectiveness in facilitating muscular capacities in different populations, there is still controversy regarding the difference between resistance training in hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Some studies have suggested that hypoxic exposure can have harmful effects on muscle tissue, reducing protein synthesis [ 54 , 84 , 85 ] and leading to muscle fiber atrophy. However, short-term hypoxic exposure, particularly when combined with resistance training, could have a reverse effect through the stimulation of muscle protein synthesis [ 86 , 87 ], which is beneficial for improving anaerobic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that hypoxic exposure can have harmful effects on muscle tissue, reducing protein synthesis [ 54 , 84 , 85 ] and leading to muscle fiber atrophy. However, short-term hypoxic exposure, particularly when combined with resistance training, could have a reverse effect through the stimulation of muscle protein synthesis [ 86 , 87 ], which is beneficial for improving anaerobic performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, from the HMS, there has been a great interrelation with diverse areas (see Figure 4). The interplay between HMS and other disciplines, such as medicine (Gamonales et al, 2023) Collaboration at an international level is crucial for the development and growth of high-quality research in HMS in developing countries like Costa Rica. By collaborating with experts from different parts of the world, researchers in Costa Rica can access cutting-edge technology, methods, and expertise.…”
Section: International and Multidisciplinary Collaborationmentioning
confidence: 99%
“…En este sentido, desde las CMH ha habido una gran interrelación con diversas áreas (ver Figura 4). La relación entre las CMH y otras disciplinas, tales como la medicina (Gamonales et al, 2023), nutrición (Capitan-Jimenez y Aragon-Vargas, 2022; Gamonales, Rojas- Gómez-Miranda et al, 2022), psicología (Gutiérrez-Vargas et al, 2021;Hernandez-Gamboa et al, 2022;Jiménez-Maldonado et al, 2018), salud ocupacional (Crowe et al, 2022;Mora et al, 2022) en Costa Rica, ha permitido a los profesionales en CMH expandir su conocimiento y crear nuevas oportunidades de investigación. Este tipo de colaboración permite la provisión de soluciones a un sector de la población desde un paradigma más amplio.…”
Section: Colaboración Internacional Y Multidisciplinariaunclassified